2019
DOI: 10.1101/699124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative Regulation of Autophagy by UBA6-BIRC6–Mediated Ubiquitination of LC3

Abstract: Although the process of autophagy has been extensively studied, the mechanisms that regulate it remain insufficiently understood. The ability to manipulate autophagy is important not only for addressing fundamental biological questions, but also for its possible application to the treatment of various human diseases. To identify novel regulators of autophagy, we performed a whole-genome CRISPR/Cas9 knockout screen in H4 human neuroblastoma cells gene-edited to express the endogenous autophagy effector LC3B fus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 100 publications
2
17
0
Order By: Relevance
“…Strikingly, the mutant P32Q showed a strong expression decrease in respect to the wildtype form, validating our predictions on the effect of P32Q mutation on LC3B stability and the neutral effects of I35V, M60V, K65E and K49N. Our results on the variants Y113C and K49N were also in line with recent papers, indicating that these mutations do not have a strong effect on protein stability [34,60,93]. Our scans predict Y113C as destabilizing the protein architecture, thus we wonder if this discrepancy could be related to the fact that the high-throughput mutational scans do not provide enough conformational sampling to model this mutation.…”
Section: Biochemical Validation Of Lc3b Mutations Effect On Protein Ssupporting
confidence: 92%
“…Strikingly, the mutant P32Q showed a strong expression decrease in respect to the wildtype form, validating our predictions on the effect of P32Q mutation on LC3B stability and the neutral effects of I35V, M60V, K65E and K49N. Our results on the variants Y113C and K49N were also in line with recent papers, indicating that these mutations do not have a strong effect on protein stability [34,60,93]. Our scans predict Y113C as destabilizing the protein architecture, thus we wonder if this discrepancy could be related to the fact that the high-throughput mutational scans do not provide enough conformational sampling to model this mutation.…”
Section: Biochemical Validation Of Lc3b Mutations Effect On Protein Ssupporting
confidence: 92%
“…Thus, our data suggest that EACC seems to accelerate the turnover of LC3 by proteasomal degradation. Indeed, it has previously been shown that LC3 is degraded by the proteasome following ubiquitination [52].…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination is another type of PTM modulating autophagy in an LC3- or GABARAP-selective manner. Monoubiquitination of LC3 (and not GABARAPs) at K51 driven by the coordinated action of ubiquitin-activating enzyme UBA6 and the hybrid ubiquitin-conjugating enzyme/ubiquitin ligase BIRC6 targets LC3 for the proteasomal degradation and negatively regulates autophagy [ 89 ]. Mib1-driven mono- and polyubiquitination of the GABARAP (not LC3) on K13 and K23 within N -terminal α-helical subdomain occurs through K48-chains and targets GABARAPs to proteasomal degradation [ 72 ].…”
Section: Ubiquitin Ubls and Atg8-family Proteinsmentioning
confidence: 99%